Penyelenggaraan Pembelajaraan Penjas Adaptif Bagi Tunanetra di Rumah pada Masa Pandemi Covid-19 (SMK N 7 Padang) - Putri Yunisya; Asep Ahmad Sopandi (Ranah Research : Journal of Multidisciplinary Research and Development, 2020)
This study aims to find out how adaptive physical education learning is implemented for blind students in class XI at SMK 7 Padang. The method used is descriptive qualitative, then analyzed and presented by concluding the data that has been collected. The implementation of adaptive physical education learning for blind students (X) at home during the Covid-19 pandemic was carried out online through a chat application, where the implementation of adaptive physical education learning the teacher provided material in the form of videos and theoretical studies related to learning material. Evaluation of activities carried out by the teacher such as giving questions after learning material and giving weekly assignments and carrying out daily tests in the form of objective questions.